A modular and efficient synthetic platform for the construction of supramolecular mono-telechelic polymers. (December 2022) - Liu, Jiaxiong; Huang, Fang; Liu, Yiliu
Abstract: Supramolecular telechelic polymers are intriguing macromolecular systems for the construction of complex supramolecular systems and responsive soft materials. In this work, we report a practical synthetic approach to preparing supramolecular mono-telechelic polymers with high efficiency and modularity. With a combination of in situ catalyst functionalization, ring-opening metathesis polymerization, and post-polymerization modification, a series of supramolecular mono-telechelic polymers with different supramolecular end-groups and sidechains are synthesized. Several selected examples are then discussed in detail to demonstrate their potential in constructing hierarchical supramolecular architectures, adaptive materials, and supramolecular biomaterials. It is highly anticipated that the synthetic approach reported here will provide rapid and controlled access to complex supramolecular polymeric systems with tailored functions. Graphical abstract: Image, graphical abstract .